EFEKTIVITAS PEMBELAJARAN REACT TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA - Yoga Adi Pratama; Nanda William (Jurnal Silogisme : Kajian Ilmu Matematika dan Pembelajarannya, 2018)
Communication is very important in the context of the 21st century, not least in the field of mathematics. REACT strategic learning consists of five stages of learning, namely relating, experiencing, applying, cooperating, and transferring is one solution for building students' mathematical communication. The aim of this study was therefore to establish differences in the mathematical communication skills of students between students who followed REACT learning strategies and who were learning conventionally. The method used in this study is quasi-experimental with a non-equivalent design of the control group. The research sample was taken using the targeted sampling method and obtained the fourth class SDN Sawah Lega 1 as the experimental group and the fourth class SDN Cikahuripan as the control group. The instruments used in this study include mathematical communication tests (pretest post test). Based on the results of the data processing, the average score of the pre-test of the control group was 32.97 and the experimental group was 31.90. After receiving another treatment, the average post-test score of the control group was 59.60 and the experimental group was 76.57. The improvement of the mathematical communication skills of students in the experimental group was higher than that of the control group, with a difference in the average post-test score of 16.97. The conclusion of this study is that the REACT strategy can be used as an alternative learning model that can be used to improve the mathematical communication skills of students.